The correct answer:
______________________________________________________
Step-by-step explanation:
______________________________________________________
Assuming you mean:
" √(9a²) + (√49b) − a + √b " ;
Simplify the expression:
_________________________________________________________
Note that: " √(9a²) = 3a " ;
"√(49b) = 7√b " ;
And we write the expression
→ " 3a + 7√b − a + √b " ;
Combine the "like terms:
" + 3a − a = 2a " ;
" + 7√b + 1√b = 8√b " ;
Rewrite:
________________________________________________________
" 2a + 8√b " ; which is: Answer choice: [C]: " 2a + 8√b " .
________________________________________________________